Culturability and viability of Salmonella typhimurium during photo-Fenton process at pH 5.5 under solar simulated irradiation - Rengifo Herrera, Julián Andrés (2013)
Culturability and viability techniques such as plate count on solid agar (PC), Most Probable Number (MPN) and Direct Viable Count-Fluorescence in Situ Hybridation (DVC FISH) were used to study the inactivation of Salmonella typhimurium by photo-Fenton process at pH 5.5. In the presence of only simulated solar irradiation (500 W·m−2), S. typhimurim showed that both culturability measured by MPN and viability (measured by DVC FISH) underwent just a slight decreasing of 2 and 1 log respectively after 240 min of light exposition while culturability measured by PC did not show any change. Results after 48 h of dark conditions did not reveal re-growth. However, when experiment was carried out in the presence of 2 mg L−1 of Fe3+ and 20 mg L−1 of H2O2 and pH 5.5, culturability was strongly affected after 240 min of simulated solar irradiation; nevertheless, viability was only slightly altered (~1 log). During dark period of 48 h changes on culturability and viability were not observed. On the other hand, it was also found that sugar metabolism was affected rather the amino-acids in S. typhimurium cells irradiated at different times upon photo-Fenton conditions. These findings might suggest for the first time that photo-Fenton process at pH 5.5 could induce viable but nonculturable state (VBNC) on waterborne S. typhimurium and that probably sugar metabolism damage could activate the VBNC state.